Faktor - Faktor Yang Mempengaruhi Financial Distress Dengan Firm Size Sebagai Variabel Pemoderasi - Stella Danica Agatha, Henryanto Wijaya (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This study aims to determine how liquidity, leverage, operating capacity, institutional ownership, independent commissioners and audit committees on financial difficulties and company size as moderators in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2017-2019. The sampling technique used was purposive sampling method with a total of 14 companies. Data processing techniques using Moderated Regression Analysis (MRA) what helped by Econometrics View (Eviews) version 11 and Microsoft Excel 2013. The results of this study are liquidity, leverage, independent commissioners and audit committee have no significant effect on financial distress, operating capacity has a significant positive effect on financial distress, institutional ownership has a significant positive effect on financial distress, firm size has a significant positive effect on financial distress, firm size moderates the effect of operating capacity and institutional ownership on financial distress, and firm size does not moderate the relationship between liquidity, leverage, and independent commissioners and an audit committee on financial distress.